How Can Small Culinary Businesses in Pedalangan Village, Banyumanik, Semarang Utilize Instagram to Grow? - Saptianing, Saptianing; Astuti, Rif’ah Dwi; Setiawan, Andi; Luthfia, Irin Mirrah; Wibowo, Bagus Yunianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The empowerment of women is a fundamental driver of economic growth and sustainable development. When women engage in business, they create more opportunities for a better life for their families. One way home-based businesses can market themselves is through social media, which is a form of online marketing that uses the Instagram platform. The main objective of this community service team is to help a group of mothers start a home business making various culinary delights in Pedalangan, Banyumanik, Semarang. Secondly, we assisted the moms' culinary business in Pedalangan in creating their own Instagram account.